Activation capacity of the intrinsic musculature of the foot in handball athletes with chronic ankle instability - García-García, D.; Llamas-Ramos, R.; Calvo-Lobo, C.; Rodríguez-Sanz, D.; San Antolín-Gil, M.; Cabanillas-García, J. L.; Sánchez-Gómez, M. C.; Llamas-Ramos, I. (Biomedicines, 2023)
Chronic ankle instability (CAI) is a common pathology in handball. The role of the intrinsic musculature of the foot in these players in relation to proprioception and stability has not been stablished. The objective of this study was to compare the ultrasound morphology of the heel fat pad of the foot in professional handball players to CAI in healthy players and establish relationships between CAI and physical and psychological variables. The study has been a descriptive observational case-control study in which 20 professional handball male players over 18 years of age were divided into 8 cases (CAI) and 12 controls (healthy). An ultrasound evaluation, the thickness and/or cross-sectional area at rest and the contraction measurement of the Abductor Digiti Minimi, Abductor Hallucis, Flexor Digitorum Brevis and Quadratus Plantae muscles were analyzed. Moreover, the compressibility index of the heel fat pad and the activation of the abdominal wall musculature (ultrasound), the flexion strength of the hallux and lesser toes (dynamometry), the foot functionality (Bristol Foot Score (BFS) questionnaire) and the psychological variables (self-reported questionnaires) were measured. There were no significant differences between the activation capacity values of the foot muscles of healthy and CAI athletes. Significant differences were found between groups regarding the BFS score (p = 0.007), d = 1.404), and significant correlations were also found between hallux flexion strength and lesser toes flexion strength in the total sample. Although there were no differences between the two groups, the identification of the activation pattern of these muscles in handball athletes is essential to the improvement of performance and preventing injuries such as CAI.